Množični zahtevki zaradi posegov v zdravo življenjsko okolje - Damjan, Matija (Pravni letopis, 2011)
Healthy living environment is one of the values protected by the Constitution of the Republic of Slovenia. Adverse environmental impacts arising from industrial and infrastructure activities are often dispersed across a wide area and affect large numbers of people. Concrete damages caused to individuals may be small, which deters the filing of individual lawsuits for damages or the prohibition of interference; the cumulative adverse impact of such activities on the natural environment and its inhabitants, however, may be significant. The article examines the possible legal mechanisms for the protection of common interests against harmful interferences in healthy living environment. These encompass both the civil law rules on the protection against excessive imissions or imminent damage risk, and the administrative rules on environmental damage. Individual action, joinder of claims, model case procedure, popular action and organizational action are discussed as procedural means for effective exercise of prohibition, mitigation and compensation claims.
Keywords: actio negatoria; actio popularis; človekove pravice; človekovo okolje; diffuse pollution; emissions; environmental damage; generally beneficial activities; healthy living environment; human rights; imisije; kvaliteta življenja; model case proceedings; negatorna tožba; okoljska škoda; onesnaževanje okolja; organizacijska tožba; organizational claim; popularna tožba; razpršeno onesnaževanje; reševanje; sodni postopek; spori; vzorčni postopek; zdravo življenje; zdravo življenjsko okolje